2016
DOI: 10.1152/ajplung.00281.2016
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of suppressing STAT3 activity in LPS-induced acute lung injury

Abstract: Acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) are diseases with high mortality. Macrophages and neutrophils are responsible for inflammatory responses in ALI and ARDS, which are characterized by excessive production of proinflammatory mediators in bronchoalveolar lavage fluid (BALF) and plasma. Aberrant activation of the JAK/STAT pathway is critical for persistent inflammation in many conditions such as infection and autoimmunity. Given the importance of the STAT3 transcription factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(112 citation statements)
references
References 67 publications
6
102
0
Order By: Relevance
“…In support of the critical role of CT-1 in mediating protection from endotoxic shock, even with high doses of LPS in vivo, we have found that repeated doses of CT-1 injected prior to high doses of LPS were able to suppress LPS-induced sepsis, as has been reported with LIF (18). In concordance with other studies, we demonstrate that CT-1 signaling regulates phosphorylation of downstream STAT-3, which is involved in signal transduction for TLR signals and proinflammatory cytokine signals (31).…”
Section: Discussionsupporting
confidence: 91%
“…In support of the critical role of CT-1 in mediating protection from endotoxic shock, even with high doses of LPS in vivo, we have found that repeated doses of CT-1 injected prior to high doses of LPS were able to suppress LPS-induced sepsis, as has been reported with LIF (18). In concordance with other studies, we demonstrate that CT-1 signaling regulates phosphorylation of downstream STAT-3, which is involved in signal transduction for TLR signals and proinflammatory cytokine signals (31).…”
Section: Discussionsupporting
confidence: 91%
“…However, the decrease of pro‐NET activity in Il17a −/− organoid could be partially restored by exogenous IL17A (Figure b,c, right panel). Because STAT3 had been reported to be involved in both acute lung injury (Gao et al, ; Zhao et al, ) and neutrophil function (Khan & Palaniyar, ; Wang et al, ; Zhang, Hwaiz, Luo, Herwald, & Thorlacius, ), we herein tested whether STAT3 was involved in the context of FlgE stimulation. As shown in Figure a–c, adding STAT3 inhibitor III, (SIn III) with FlgE in WT lung organoid culture decreased the pro‐NET activity.…”
Section: Resultsmentioning
confidence: 99%
“…More activation of STAT3 induces more expression of cytokine expression. Blocking STAT3 activation by small‐molecule STAT3 inhibitor (LLL12) can suppress the expression of IL‐1beta, IL‐6, TNF‐alpha, iNOS, CCL2 and MHC class II in macrophages and inflammatory cells from LPS‐induced ALI mouse model, indicating the pro‐inflammatory function of STAT3 . It is known that SOCS3 is a negative regulator of STAT3.…”
Section: Introductionmentioning
confidence: 99%
“…Blocking STAT3 activation by small-molecule STAT3 inhibitor (LLL12) can suppress the expression of IL-1beta, IL-6, TNF-alpha, iNOS, CCL2 and MHC class II in macrophages and inflammatory cells from LPS-induced ALI mouse model, indicating the pro-inflammatory function of STAT3. 19 It is known that SOCS3 is a negative regulator of STAT3. Activation of STAT3 induces transcriptional up-regulation of SOCS3 and subsequently suppresses STAT3 activation in the inflammatory condition.…”
mentioning
confidence: 99%